Playing with Perceptions: Reducing Mental Health Stigma through Proxy Experiences in Video Games: Insights and Recommendations from Self-Identified Gamers Using Hellblade: Senua’s Sacrifice (2017) as a Case Study - Pierce, Luke Simeon (Loading, 2025)
This pilot study examines how self-identified gamers perceive video games as tools for reducing public stigma around mental health issues (MHIs) using a sequential, linked mixed-methods design. A closed online survey (N = 50) assessed demographics, gaming/media engagement, and attitudes toward MHI representation and served as the recruitment pool for an in-person qualitative phase, in which a subset completed individual playtests of Hellblade: Senua’s Sacrifice (2017) followed by semi-structured interviews (n = 7).Participants across both phases supported the use of video games for destigmatization. Playtesters emphasised that stigma-reduction impacts are more plausible when designers prioritise engaging narrative design, immersive play, and meaningful player autonomy over overt, moralizing, or didactic instruction. They linked Hellblade’s authenticity and ethical representation to the proactive collaboration between developers, mental health professionals, and people with lived experience of MHIs. They also advocated for wider consultation with related affected groups (e.g., family members) to better reflect the cumulative and far reaching societal impacts of mental health issues.Three developer-oriented recommendations emerged: define target audiences beyond “gamers” alone; design research-informed games that balance compelling play with sensitive portrayal; and disseminate across several platforms concomitantly to reach active players, wider gaming-related communities, and non-gaming publics.